Adsorption of Free Fatty Acids in Crude Palm Oil (CPO) Using Chicken Egg Shells - Marsela Marsela; Adhitiyawarman Adhitiyawarman; Anthoni Batahan Aritonang (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Chicken eggshell waste represents an abundant biomineral resource that can be converted into calcium oxide (CaO) to provide a low cost and environmentally friendly adsorbent for crude palm oil (CPO) refining. This study examined the effects of calcination temperature (800 and 850 °C), sodium bicarbonate (NaHCO3) activator concentration (3, 4, and 5%), and adsorbent mass (0.1, 0.5, and 0.9 g) on the adsorption of free fatty acids (FFA) from CPO. Eggshell derived CaO was produced by calcination and chemical activation, and phase formation was verified using X ray diffraction (XRD). Adsorbent quality was screened using iodine adsorption capacity, which peaked at 509.83 mg/g for CaO activated with 4% NaHCO3. XRD patterns showed that calcination at 850 °C yielded more crystalline CaO than calcination at 800 °C, supporting selection of 850 °C for subsequent activation and adsorption tests. Batch adsorption demonstrated that higher adsorbent dosage increased FFA removal, with 0.9 g providing the best performance. Under the optimum condition, FFA decreased from 12.16% to 3.08%, corresponding to 74.70% adsorption efficiency and meeting the Indonesian standard SNI 2901 2021 (maximum FFA 5%). These findings highlight chicken eggshell derived CaO as a promising, waste based substitute for commercial adsorbents in sustainable CPO purification.